Lifestyle Modification after Diagnosis of Hypertension in Patients Visiting Lumbini Medical College Teaching Hospital - Nepal, Parbati; Dhungana, Bina (Journal of Lumbini Medical College, 2016)
Introduction: Lifestyle modifications is an important aspect of hypertension therapy. However, studies on this non-pharmacological approach of hypertension management and its impact is very limited in a developing country like Nepal. The objective of the present study was to determine the life style of patients after diagnosis of hypertension. Methods: A descriptive cross sectional study design was conducted in Lumbini Medical College Teaching Hospital (LMCTH). A total of 63 patients attending Medical outpatient clinic of Lumbini Medical College who were diagnosed as hypertensive at least two months before the interview were included. Data were collected from 22nd February 2015 to 21st March 2015 by interview method using a questionnaire consisting of a combination of structured and semi-structured questions. Results: This study revealed that non-vegetarian decreased from 95.2% to 74.6% after diagnosis. Lifestyle modification criteria like amount of salt intake, smoking, and alcohol consumption were significantly reduced whereas physical exercise and stress reduction activity were significant increased. Conclusion: Majority of respondents has changed their lifestyle after diagnosis of hypertension. DOI: https://doi.org/10.22502/jlmc.v3i1.62